To analyze the function \( f(x) = x^2 - 3x + 2 \), let's evaluate it at specific points and find the y-intercept.
-
Finding \( f(0) \): \[ f(0) = 0^2 - 3(0) + 2 = 2 \]
-
Finding \( f(1) \): \[ f(1) = 1^2 - 3(1) + 2 = 1 - 3 + 2 = 0 \]
-
Finding \( f(2) \): \[ f(2) = 2^2 - 3(2) + 2 = 4 - 6 + 2 = 0 \]
-
Finding the y-intercept: The y-intercept occurs when \( x = 0 \), which we already calculated. Thus, the y-intercept is: \[ (0, f(0)) = (0, 2) \]
Summary of Results:
- \( f(0) = 2 \)
- \( f(1) = 0 \)
- \( f(2) = 0 \)
- The y-intercept is \( (0, 2) \).